Implementasi Pengembangan Soft Skill Mahasiswa Pgmi Dalam Pembelajaran Sains Di Min 1 Wonosari Yang Bervisi Karakter Bangsa - Agung Rokhimawan, Moh. (Universitas Alma Ata, 2013)
The development of science and technology today is very fast, it can not be dammed again, and in fact all elements of society feel the impact of these developments. With the advancement of science and technology now Indonesian society in general forced to literacy Saintek to sustain life in the present and future. The results of a survey conducted in the UK showed that about 30 % of workers use science in some aspects of his work . This situation is expected to continue to increase from year to year . The results of a similar survey also showed that competence is most often used by workers is the competence to solve problems, work in teams, and communicate . The second survey showed a similar thing, which both point to the same three competencies : problem solving, working in teams, and communicate . It's all included components Soft Skill. The method used is the method of development up to implementation. demonstrated that the results of observation in science learning that has been implemented in MIN 1 Wonosari got an average score of 115 with a good category